The Traditions and Thoughts of Sundanese Religious Figure KH.R. Muhammad Nuh Bin Idris in Religious Moderation Education - Budi Utomo; Mudzakkri Ali; Ghufron Hamzah; A. Umar (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2026)
Amidst the diversity of beliefs in life, harmony is a life goal that must be maintained and nurtured. Religious moderation offers a solution for coexistence and mutual assistance. However, amidst cultural diversity, especially beliefs, the government will not be successful without collaborating with community and religious leaders. Synergy between the government, religious and community leaders is necessary, so that an understanding of religious moderation is fully conveyed and practiced by the community at the grassroots level. This study aims to examine the role models and thoughts that have a significant impact on religious moderation education from a Sundanese religious figure, namely KH.R. Muhammad Nuh Bin Idris. The method used in this study is library research through a qualitative approach. Data collection was carried out through a literature review of both primary data such as his work Al-Ajwibatus Syafiyah li Dzawil 'Uqulis and secondary data. The results of this study indicate that the role of figures in broadcasting and disseminating the values ​​or understanding of religious moderation is very effective and has a significant impact on the lives of the community. This is influenced by a figure whose life serves as a central role model, a guiding principle, and a source of solutions in life. A figure's life revolves around the community or congregation almost 24 hours a day, even until death.